Executive function and pre-academic skills in preschoolers from South Africa - Caylee J. Cook; Steven Howard; Gaia Scerif; Rhian Twine; Kathleen Kahn; Shane Norris; Catherine Draper (My University, 2023)
Background: While there is now considerable evidence in support of a relationship between executive function (EF) and academic success, these findings almost uniformly derive from Western and high-income countries. Yet, recent findings from low- to middle- income countries have suggested that patterns of EF and academic skills differ in these contexts, but there is little clarity on the extent, direction and nature of their association. Aim: This study aimed to investigate the contribution of EF to pre-academic skills in a sample of preschool children (N = 124; Mage = 50.91 months; 45% female). Setting: Two preschools were recruited from an urban setting in a community with both formal and informal housing, overcrowding, high levels of crime and violence, and poor service delivery. Three preschools were recruited from rural communities with household plots, a slow rate of infrastructure development, reliance on open fires for cooking, limited access to running water and rudimentary sanitation. Methods: Pre-academic skills were assessed using the Herbst Early Childhood Development Criteria test, and EF was assessed using the Early Years Toolbox. Results: Although EF scores appeared high and pre-academic skills were low (in norm comparisons), EF inhibition (ß = 0.23, p = 0.001) and working memory (ß = 0.25, p < 0.001) nevertheless showed strong prediction of pre-academic skills while shifting was not significant. Conclusion: While EF is an important predictor of pre-academic skills even in this low- and middle-income country context, factors in addition to EF may be equally important targets to foster school readiness in these settings. Contribution: The current study represents a first step towards an understanding of the current strengths that can be leveraged, and opportunities for additional development, in the service of preparing all children for the demands of school.
Keywords: preschool; school readiness; executive function; early years toolbox; pre-academic skills; low-income.